New transiting hot Jupiters discovered by WASP-South, Euler/CORALIE, and TRAPPIST-South. Issue 1 (9th October 2018) - Hellier, Coel; Anderson, D R; Bouchy, F; Burdanov, A; Cameron, A Collier; Delrez, L; Gillon, M; Jehin, E; Lendl, M; Nielsen, L D; Maxted, P F L; Pepe, F; et al.
ABSTRACT: We report the discovery of eight hot-Jupiter exoplanets from the WASP-South transit survey. WASP-144b has a mass of 0.44 M Jup, a radius of 0.85 R Jup, and is in a 2.27-d orbit around a V = 12.9, K2 star which shows a 21-d rotational modulation. WASP-145Ab is a 0.89 M Jup planet in a 1.77-d orbit with a grazing transit. The host is a V = 11.5, K2 star with a companion 5 arcsec away and 1.4 mag fainter. WASP-158b is a relatively massive planet at 2.8 M Jup with a radius of 1.1 R Jup and a 3.66-d orbit. It transits a V = 12.1, F6 star. WASP-159b is a bloated hot Jupiter (1.4 R Jup and 0.55 M Jup ) in a 3.8-d orbit around a V = 12.9, F9 star. WASP-162b is a massive planet in a relatively long and highly eccentric orbit (5.2 M Jup, P = 9.6 d, e = 0.43). It transits a V = 12.2, K0 star. WASP-168b is a bloated hot Jupiter (0.42 M Jup ; 1.5 R Jup ) in a 4.15-d orbit with a grazing transit. The host is a V = 12.1, F9 star. WASP-172b is a bloated hot Jupiter (0.5 M Jup ; 1.6 R Jup ) in a 5.48-d orbit around a V = 11.0, F1 star. WASP-173Ab is a massive planet (3.7 M Jup ) with a 1.2 R Jup radius in a circular orbit with a period of 1.39 d. The host is a V = 11.3, G3 star, being the brighter component of the double-star system WDS23366 − 3437, with a companion 6 arcsec away and 0.8 mag fainter. One of the two stars shows a rotational modulation of 7.9 d.